Enhancing foam stability in porous media by applying nanoparticles. Issue 5 (4th May 2018) - Wang, Shengbo; Chen, Changlong; Kadum, Mohannad J.; Shiau, Bor-Jier; Harwell, Jeffrey H.
ABSTRACT: Several new foaming agent formulations (surfactants and polymers) in the presence of multi-walled carbon nanotube (MWCNT) were developed in 3% salinity (NaCl, 2.4 wt%, CaCl2, 0.6 wt%). The dispersion stability of the MWCNT and the viscosity of the solutions were examined as a prerequisite for reservoir applications. Foam was generated in situ and one-dimensional flow-through tests were performed by co-injecting air and foaming solution either in the presence of MWCNT or at particle-free condition. The pressure drop (Δ p ) across the sand-pack and the nanoparticles breakthrough were closely monitored. The fluid injection rate, gas fraction, and the effect of MWCNT on foams in porous media were investigated. Our results reveal that foams stabilized by the selected nanoparticles are capable of generating stronger foams leading to higher apparent Δ p . The Δ p profile varies with gas fraction, which largely affects the foam texture and quality. Also, the viscosity of foaming agent solutions influences Δ p values. Adding MWCNT to the foaming agent solutions appears beneficial to the flooding as surfactants adsorption onto nanoparticle surfaces, which facilitates surfactants partitioning to the G/L interface. Addition of nanoparticles in the developed foam formulations leads to the formation of high-quality stronger foams in porous media, which could potentially improve the sweep efficiency and increase the oil recovery. GRAPHICAL ABSTRACT: